Dziennikarskie sposoby wywierania wpływu na odbiorcę w telewizyjnych serwisach informacyjnych - Rutkowska, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Agnieszka Rutkowska’s “Journalistic methods of influence on viewer in television news programmes” is an authorial analysis of major news broadcasts on what are the most popular TV stations according to viewership data. The author compares textual issues, as well as the non-verbal level of television materials realised during the same time and describing the same subject. The reporters’ techniques may have been used to influence news recipients.